Metode Pembelajaran Pendidik Profesional dalam Alquran - Arlina Arlina; Cici Rusmaida; Nurhayati Bako; Priska Priska; Hafizurrahim Nasution (-, 2023)
Islamic education learning methods are inseparable from the main sources of Islamic teachings, namely the Koran and Hadith. The Al-Qur'an as a guide and guide for humans has provided guidelines in education, especially regarding learning methods. This method is used together with the personal approach of the teacher and students, so that students are interested and like what is being taught. It is difficult to succeed in studying when student enthusiasm is weak. Therefore, professional educators must be smart and creative in choosing the right method. The method of this Learning System series plays an important role in the success of the learning process. The method is a prerequisite for achieving educational goals.